Die deutsche Neue Linke im Spiegel der USA - Mayer, Margit (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1993)
A comparison of the German and US Sixties Movements points to the role different political opportunity structures have played both in shaping the concrete form and direction of the protest in each country, and in the interpretations of the role and effects of these movements on society. The comparison with the US case sheds doubt on the widespread claim that '68 has »fundamentally liberalized« and »modernized« German society.